Summertime Chlorophyll a and Particulate Organic Carbon Standing Stocks in Surface Waters of the Fram Strait and the Arctic Ocean (1991–2015) - Nöthig, Eva-Maria; Ramondenc, Simon; Haas, Antonie; Hehemann, Laura; Walter, Andreas; Bracher, Astrid; Lalande, Catherine; Metfies, Katja; Peeken, Ilka; Bauerfeind, Eduard; Boetius, Antje (Frontiers in Marine Science, 2020)
Sea ice in the Arctic Ocean has been undergoing dramatic changes during the last two decades. In addition, the water temperature of the inflow of Atlantic water masses at the gateway Fram Strait has recently increased. Long-term data may help to evaluate the impact of these physical changes on the biological processes in surface waters. Over a 25-year period, and mostly in summer, water samples were collected at discrete depths within the uppermost 100 m of the Fram Strait and other regions of the Arctic Ocean (AO) to investigate chlorophyll a (Chl a) and particulate organic carbon (POC) standing stocks. Stations sampled from 1991 to 2015 were located in the Fram Strait, Barents Sea, on the Eurasian shelf, and over the Nansen, Amundsen, and parts of the Amerasian basins. Discrete Chl a and POC measurements obtained during 33 and 24 expeditions, respectively, were integrated over the upper 100 m of the water column to monitor spatial and interannual variations in distribution patterns of standing stocks. In general, the highest Chl a and POC standing stocks were observed in the eastern Fram Strait and in the Barents Sea, while the lowest biomasses were observed in the heavily ice-covered regions of the central AO, mainly in the Amundsen and Amerasian basins. Whereas summertime Chl a stocks sharply decreased northwards from the Fram Strait and Barents Sea towards high latitudes, the decline in POC standing stocks was less pronounced. Over the sampling period, summertime Chl a stocks slightly increased in the eastern Fram Strait but remained more or less constant in the central AO. In contrast to Chl a, standing stocks of POC eventually increased over the last 25 years in the central AO, possibly as an effect of increasing air temperatures, decreasing sea ice extent and thickness, and increasing light availability. Moreover, variations in riverine discharge and in sea ice export within the Transpolar Drift may have contributed to the enhanced POC stock in the central AO surface waters.